2004
DOI: 10.1080/00365510410004876
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a peanut agglutinin test and an immunochemical faecal occult blood test in detecting colorectal neoplasia in symptomatic patients

Abstract: A single PNA test in its present form is as sensitive an indicator of colorectal neoplasia as Hemolex completed over three days, but lacks specificity. The 160 kD cancer-associated antigen we have identified is under further characterization for development of a more specific PNA test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…As a result, age-related differences in survival disappeared, indicating that probably colorectal cancer itself is not the main cause of age-related differences in survival. This is in line with earlier studies that found no age-related differences in cancer-specific survival 57. However, this remains intriguing, since many papers indicate that differences in survival between the young and the elderly can be attributed to undertreatment in the elderly 1,9.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As a result, age-related differences in survival disappeared, indicating that probably colorectal cancer itself is not the main cause of age-related differences in survival. This is in line with earlier studies that found no age-related differences in cancer-specific survival 57. However, this remains intriguing, since many papers indicate that differences in survival between the young and the elderly can be attributed to undertreatment in the elderly 1,9.…”
Section: Discussionsupporting
confidence: 91%
“…Notwithstanding all these differences, several studies found similar disease-specific survival for elderly and young colorectal cancer patients 57. This would indicate that the excess mortality in elderly colorectal cancer patients is due to competing causes of death.…”
mentioning
confidence: 95%
“…18 articles fulfilled our inclusion criteria. 11 , 12 , 13 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Of them, three studies 12 , 23 , 24 were obtained by cross referencing.…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding all these differences, several studies found similar disease-specific survival for elderly and young colorectal cancer patients [13,14]. This would indicate that the increase of mortality in elderly colorectal cancer patients is due to competing causes of patients: the age ≥ 85 y (p=0.005), the ASA III-IV score (p=0.002), the history of cardiac disease (p=0.047), the emergency admittance (p<10 -3 ), the bowel obstruction (p<10…”
Section: Discussionmentioning
confidence: 98%